Case Report: Durable complete response of metastatic hepatocellular carcinoma with asymptomatic hyperamylasemia to combined immunotherapy of anti-cytotoxic T lymphocyte-associated antigen 4 plus anti-programmed cell death-1 antibodies - Gao, Han; Chang, Rui-zhi; Chen, Xiao-ping; Zhang, Wan-guang; Zhang, Bixiang; Luo, Xin; Ding, Ze-yang (Frontiers in Immunology, 2023)
Background: Combined immunotherapy has shown promising results in the treatment of advanced HCC, whereas the priority population that would respond to the combined immunotherapy is still elusive. In addition, HCC with asymptomatic hyperamylasemia was not reported previously.Case presentation: An aged patient was diagnosed as HCC with BCLC stage C (bone metastasis).Notably, this patient showed asymptomatic hyperamylasemia. The patient was then enrolled in a trial evaluating combined immunotherapy of anti-PD-1 antibody sintilimab (IBI308) plus anti-CTLA-4 antibody (IBI310) in advanced HCC. After being treated with combined immunotherapy, this patient rapidly achieved complete response (CR) according to mRECIST criteria or immune partial response (iPR) according to iRECIST criteria and maintain the CR state for more than 12 months. Interestingly, serum levels of amylase and lipase in this patient were reduced after treatment.We reported, for the first time, a case of metastatic HCC with asymptomatic hyperamylasemia, and suggested that HCC patients with asymptomatic hyperamylasemia may benefit from combined immunotherapy of anti-CTLA-4 and PD-1 antibodies.